Potential of Biomass to Liquid-, Hydrotreated Vegetable Oils-, and Fatty Acid Methyl Esters-Blends for Diesel Engines in Passenger Cars - Moeltner, Lukas; Schallhart, Verena (Frontiers in Mechanical Engineering, 2020)
Diesel engines, in combination with modern turbocharging and common rail injection systems, feature comparably high efficiencies coupled with favorable torque characteristics. Therefore, besides the utilization in commercial vehicles, diesel engines gained large market shares within the passenger car sector. The European Union regulates the deployment of biofuels and has issued several targets throughout the years; focusing on the urge to reduce carbon dioxide emissions, as well as on the growing demand for independence of fossil energy sources. This contribution presents investigations on fuel blends containing different shares of biomass to liquid, hydrotreated vegetable oils, and fatty acid methyl ester applied in a state of the art light-duty diesel engine. In general, the reviewed fuel blends exhibit good applicability for the utilization in the test engine with default settings of injection timing and exhaust gas recirculation; adjustments on the just mentioned parameters unveil further potential in terms of emissions and efficiency. Particularly the potential of biomass to liquid blends to partly mitigate the tradeoff between particulate matter and nitrogen oxides deserves distinct attention.